Corruption in the Perspective of Islamic Criminal Law and Indonesian Criminal Law Reform - Yoyok Adi Syahputra (ISNU Sumatera Utara, 2026)
Corruption is a multidimensional problem that not only harms the state's finances, but also damages the moral, social, and justice order of society. In an Islamic perspective, corruption is seen as a despicable act that is contrary to the principles of trust and justice, although the term corruption is not found explicitly in classical jurisprudence literature. The Qur'an and Sunnah have substantively regulated the prohibition of acts that have a corrupt character through the concepts of ghulul, thioniah, risywah, ghasab, and unlawful possession-eating. This condition requires the formulation of anti-corruption fiqh that is contextual and relevant to modern legal challenges. This research aims to analyze the concept of corruption from the perspective of Islamic criminal law and formulate anti-corruption jurisprudence with the approach of maqāṣid al-syarī'ah, as well as examine its relevance to the Indonesian criminal law system. The research method used is normative legal research with a conceptual, philosophical, and legislative approach, through the study of the Qur'an, Sunnah, fiqh rules, classical and contemporary fiqh literature, as well as laws and regulations related to corruption. The results of the discussion show that corruption in Islamic criminal law is more appropriately qualified as jarīmah ta'zīr because it does not have explicit sanctions in nash, but it has a broad and systemic impact. The principles of maqāṣid al-syarī'ah place corruption as a serious violation of the protection of property and even human souls. Corruption eradication regulations in Indonesia's positive law are basically in line with the principle of ta'zīr as long as it is oriented towards the public good. This study concludes that the integration of anti-corruption fiqh values with national criminal law is a strategic step in realizing the rule of law that is just and based on moral and social values.